IMPLEMENTASI MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN DI SMK NEGERI 5 KENDAL - Eko Hery Saputro; Nina Oktarina; Fathur Rohman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article describes a descriptive qualitative reseach on the leadership style of the principal of SMK Negeri 5 Kendal in improving the quality of education. This article discusses the implementation of educational management and leadership at SMK Negeri 5 Kendal. Education has an important role in shaping the nation's future, and educational leaders play a vital role in managing educational institutions. This report aims to identify educational leaders at SMK Negeri 5 Kendal and their contribution to the quality of education. Through observations and interviews with school principals, teachers and students, it was found that educational management includes curriculum planning, human resource management, as well as monitoring and evaluation. However, challenges such as lack of government support, minimal training for school principals, and teacher resistance to change are still faced. Improvement efforts through professional training, better communication, and implementation of school-based management are proposed to increase the effectiveness of educational management and leadership. Observation results show that although challenges exist, the innovations implemented have a positive impact on the learning process and student achievement.